2022
DOI: 10.3390/land11020243
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment and Physical Activity among Adults in Hong Kong: Role of Public Leisure Facilities and Street Centrality

Abstract: Physical inactivity has been identified as the fourth leading risk factor for global mortality, and has been shown to be related to the built environment. To fill the literature gap from a non-Western setting, we examined: (1) the associations between the built environment and physical activity (PA) behaviors, (2) how the association of street centrality with PA is mediated by public leisure facilities, and (3) whether the association of the built environment with PA differs among people with different perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…A study in Hong Kong indicates that 75% of recreational walking of older people takes place in POS within the neighborhood, with 42% occurring in parks and 32% occurring on the street [ 47 , 48 ]. Living near urban parks is associated with less likelihood of sedentary behaviors [ 49 ]. Older people perceive POS as places for play and recreation, such as stretching and exercise [ 50 , 51 ].…”
Section: Literature Review: From Pos To Multifaceted Well-beingmentioning
confidence: 99%
“…A study in Hong Kong indicates that 75% of recreational walking of older people takes place in POS within the neighborhood, with 42% occurring in parks and 32% occurring on the street [ 47 , 48 ]. Living near urban parks is associated with less likelihood of sedentary behaviors [ 49 ]. Older people perceive POS as places for play and recreation, such as stretching and exercise [ 50 , 51 ].…”
Section: Literature Review: From Pos To Multifaceted Well-beingmentioning
confidence: 99%
“…The results showed that a very high proportion of participants (94%) did not meet the WHO's adult physical activity recommendations of at least 75 min per week of vigorous-intensity or 150 min of moderate-intensity aerobic physical activity [11]. Although it is well documented that many Hong Kong adults have more sedentary lifestyles than their Western counterparts [12], caution must be taken in interpreting the results. First, data collection took place during the COVID-19 pandemic, when wearing a mask was mandatory in all public areas.…”
Section: Discussionmentioning
confidence: 99%
“…Data on sports facilities were collected from the Leisure and Cultural Service Department, Hong Kong ( (accessed on 12 December 2021). Sports facilities were defined as sports center, recreation grounds, water sports centers, swimming pools, or sports grounds [ 26 ]. We did not use individually listed sports facilities because they are provided by relevant place.…”
Section: Methodsmentioning
confidence: 99%
“…Specific to obesity-related environmental intervention research, the improvement of food and physical activity environments has been proven to contribute to healthier eating and physical activity behaviors by a large number of studies [ 23 , 24 , 25 ]. Sports facility density was found to be related to physical activity behavior, and greenery correlated with sedentary behavior [ 26 , 27 ]. The local retail food environment was also found to be related with dietary behaviors in Hong Kong by one of our former studies [ 28 ].…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation